New Technological Approaches for Dental Caries Treatment: From Liquid Crystalline Systems to Nanocarriers - Luiz, Marcela Tavares [UNESP]; di Filippo, Leonardo Delello [UNESP]; Dutra, Jessyca Aparecida Paes [UNESP]; Viegas, Juliana Santos Rosa; Silvestre, Amanda Letícia Polli [UNESP]; Anselmi, Caroline [UNESP]; Duarte, Jonatas Lobato [UNESP]; Calixto, Giovana Maria Fioramonti [UNESP]; Chorilli, Marlus [UNESP] (MDPI, 2023)
Dental caries is the most common oral disease, with high prevalence rates in adolescents and low-income and lower-middle-income countries. This disease originates from acid production by bacteria, leading to demineralization of the dental enamel and the formation of cavities. The treatment of caries remains a global challenge and the development of effective drug delivery systems is a potential strategy. In this context, different drug delivery systems have been investigated to remove oral biofilms and remineralize dental enamel. For a successful application of these systems, it is necessary that they remain adhered to the surfaces of the teeth to allow enough time for the removal of biofilms and enamel remineralization, thus, the use of mucoadhesive systems is highly encouraged. Among the systems used for this purpose, liquid crystalline systems, polymer-based nanoparticles, lipid-based nanoparticles, and inorganic nanoparticles have demonstrated great potential for preventing and treating dental caries through their own antimicrobial and remineralization properties or through delivering drugs. Therefore, the present review addresses the main drug delivery systems investigated in the treatment and prevention of dental caries.
Keywords: buccal administration; drug delivery systems; nanotechnology; oral biofilm; remineralization